THE INTERPLAY BETWEEN PHYSIOTHERAPIST AND EXERCISE PHYSIOLOGIST IN THE EXERCISE ONCOLOGY PROGRAM - Fernando Tadeu Trevisan Frajacomo; Rafael Deminice (Journal of Physical Education)
ABSTRACT Exercise is a relevant tool in the oncology rehabilitation program due to restoring functional capacity, improving quality of life, and preventing early cancer mortality, mainly in unfit cancer patients. According to a systematic physical evaluation and risk stratification model, exercise physiologists (or equivalent) and physiotherapists with additional cancer exercise training are candidates to provide and supervise exercise to cancer survivors. However, the referral pathways are unclear, and a few cancer survivors are educated about personalized exercise oncology programs. This article aims to engage and stimulate additional training of Exercise physiologists and Physiotherapists in a collaborative exercise oncology program and proposes a dynamic and supervised model to attend to the emerging multidisciplinary scenario of cancer.